Bioprospecção de enzimas e biossurfactantes de interesse industrial produzidos por fungos presentes em sedimentos do Lago Boeckella, Baía Esperança, nordeste da Península Antártica - Elisa Amorim Amâncio Teixeira (2024)
Antarctica is characterized by its different extreme conditions, such as low temperatures, low nutrient availability, strong winds, high levels of UV radiation, high salinity and pH variations. Microorganisms capable of surviving these extreme conditions have attracted great biotechnological interest in recent years due to their ability to produce different bioactive metabolites, whose advantages are stability, regular supply and, in many cases, low toxicity, when compared to other substances. traditional synthetic materials used in industries. Considering the diverse biotechnological applications of microorganisms found in Antarctica, this work aimed to characterize cultivable fungi present in sediments from Lake Boeckella, located in Hope Bay, northeast of the Antarctic Peninsula, and evaluate them for the production of enzymes and biosurfactants of industrial interest. The fungi were obtained from sediments from two cores, corresponding to the western and southeastern margins of Lake Boeckella, using the culture media Dicloran Rose Bengal Agar, Dicloran Glycerol Agar, Minimum Medium and Malt Extract Medium, and the plates were incubated at 15 ºC for 60 days. 116 fungal isolates were obtained (86 filamentous and 30 yeast), of which 104 were identified. The 16 genera identified belong to the phyla Ascomycota (56.25%), Basidiomycota (37.5%) and Mortierellomycota (6.25%). The lake, in general, presented high diversity and richness, and moderate dominance. To detect the enzymes, the isolates were cultivated in specific media for each enzyme studied and the taxa that presented an Enzyme Index (EI) ≥ 2 were considered good producers. Of the filamentous fungi, only isolated from Ramgea cf. ozimecii presented EI ≥ 2. As for yeasts, isolates of the taxa Holtermanniella wattica, Leucosporidium creatinivorum, Leucosporidium sp., Mrakia blollopis, Naganishia sp. and Phenoliferia sp. presented EI ≥ 2 for more than one enzyme. The isolate Naganishia sp. (UFMGCB 19775) presented the highest EI (4.03 ± 0.08). To analyze the production of biosurfactants, each isolate was inoculated in a medium composed of sunflower oil and yeast extract and incubated at 20 °C under agitation for nine days and, after 24 hours, the emulsification test was performed. Isolates that showed an average emulsification index (E24%) > 50% were classified as satisfactory producers of biosurfactants. Regarding filamentous fungi, 16 isolates presented E24% > 50%, which were identified as Antarctomyces psychrotrophicus (08 isolates), Cosmospora sp. (02), Pseudogymnoascus sp. (02), R. cf. ozimecii (01), Thelebolus sp. (01) and two isolates that were not identified. Among the producing isolates, three isolates of A. psychrotrophicus presented values above 80%, which were higher than synthetic surfactant (SDS). As for yeasts, “Candida davisiana” (07 isolates) and Cystobasidium sp. 2 (01) presented E24% > 50%. In this way, this work contributes to the understanding of the cultivable fungal diversity of Lake Boeckella, which suffers from the consequences of local climate change. Furthermore, it highlights the importance of taxonomic diversity and the ecological role that these microorganisms play in Antarctic lake environments, in addition to their biotechnological potential in terms of the production of enzymes and biosurfactants at low temperatures.